Cytogenetic impact of gamma radiation and its effects on growth, yield and drought tolerance of maize (Zea mays L.) - Walaa M. Al-Sayed; Hanaa H. El-Shazly; Awatif I. El-Nahas; Ahmed A. A. Omran (BMC Plant Biology)
Abstract Maize is the third most important grain crop worldwide after wheat and rice; it is a vital global crop, serving as a key source of food, animal feed, and industrial products, making it essential for food security and economic stability in many countries. Drought stress adversely affects water uptake and can stunt growth, reducing the overall productivity of maize. So, this study was carried out to investigate the cytogenetic effects of gamma radiation and drought stress on maize SC131 genotype, focusing on chromosomal aberrations in seedling root meristems induced by varying doses of gamma irradiation (50, 100, 150, 200, and 250 Gray) and drought stress imposed by 10% polyethylene glycol (PEG). The present study also aims to evaluate the impact of these treatments on growth parameters under a controlled pot experiment. Additionally, molecular polymorphism induced by both gamma irradiation and drought stress was analyzed using Real-Time quantitative PCR techniques for DREB2, ERF, and EF transcription factors. Also, under a field condition experiment, maize plants were subjected to the same gamma irradiation doses and drought stress by reducing the number of irrigations, with subsequent evaluations of yield attributes to assess the overall impact of treatments on plant performance. The study also investigates the sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) banding patterns of proteins in grains yielded under the influence of gamma radiation and drought treatments. Findings of the current investigation indicate that the low dose of gamma radiation (50 Gray) not only induces cytogenetic changes but also enhances drought tolerance and improves yield characteristics, suggesting that targeted gamma irradiation could serve as a viable strategy to bolster maize resilience in challenging environmental conditions.